Nonlinear dynamics induced by parallel and orthogonal optical injection in 1550 nm Vertical-Cavity Surface-Emitting Lasers (VCSELs) - Hurtado, Antonio; Quirce, Ana; Valle, Angel; Pesquera, Luis; Adams, Michael J. (Optics express, 2010)
We report a first experimental study of the nonlinear dynamics appearing in a 1550 nm single-mode VCSEL subject to parallel and to orthogonal optical injection. For the first time to our knowledge we report experimentally measured stability maps identifying the boundaries between regions of different nonlinear dynamics for both cases of polarized injection. A rich variety of nonlinear behaviours, including periodic (limit cycle, period doubling) and chaotic dynamics have been experimentally observed.